2017
DOI: 10.1063/1.4984786
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of ion temperature effects to the plasma wall transition using a one-dimensional two-fluid model. I. Finite Debye to ionization length ratio

Abstract: A one-dimensional, two-fluid, steady state model is used for the analysis of ion temperature effects to the plasma-wall transition. In this paper, the model is solved for a finite ratio between the Debye and the ionization length, while in Part II [T. Gyergyek and J. Kovačič, Phys Plasmas 24, 063506 (2017)], the solutions for [Formula: see text] are presented. Ion temperature is treated as a given, independent parameter and it is included in the model as a boundary condition. It is shown that when the ion temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Then, the zeta potentials at different concentrations of additional ions were measured to understand the ions’ effect on motion and interaction of colloidal particles. It was found that the added Na + or Cl – would also align around the charged cefradine nanocrystals by ion diffusion and electrostatic attraction, which will push the previous ions out of the diffusion layer by electrostatic repulsion, and the diffusion layer will become thinner (Figure c). , Besides, the large amounts of ions could promote the formation of ionic groups, which will lead to the net shielding effect and weaken the charge of particles . Therefore, the effective zeta potential will decrease with the addition of NaCl, and the shielding effect is maximized for 0 mV at 28 mM (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the zeta potentials at different concentrations of additional ions were measured to understand the ions’ effect on motion and interaction of colloidal particles. It was found that the added Na + or Cl – would also align around the charged cefradine nanocrystals by ion diffusion and electrostatic attraction, which will push the previous ions out of the diffusion layer by electrostatic repulsion, and the diffusion layer will become thinner (Figure c). , Besides, the large amounts of ions could promote the formation of ionic groups, which will lead to the net shielding effect and weaken the charge of particles . Therefore, the effective zeta potential will decrease with the addition of NaCl, and the shielding effect is maximized for 0 mV at 28 mM (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Also the plasma is symmetrical around the central plane z = 0 ; therefore, it is studied in the half-space 0 ≤ z ≤ L . Then, the two-fluid model of plasma is represented by [16,21,30,32,34,36];…”
Section: Model and Equationsmentioning
confidence: 99%
“…We have done the computations with = 108.0832 calculated for the electropositive gas Argon. Relation (34) is known as the floating condition and f is called the floating potential.…”
Section: Asymptotic and Full Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluks partikel berhubungan dengan kecepatan hanyut (198; 200; 201; 203; 204), dengan: J = sc (14) Hubungan ini merupakan kelanjutan dari argument yang sudah kita gunakan beberapa kali sebelumnya. Jadi, semua partikel dalam jarak s∆ t A, dapat melewati jendela dengan luas A dalam selang waktu ∆ t (205)(206)(207)(208)(209). Dengan demikian, jumlah mol dapat lewat dalam selang waktu itu adalah: s∆ t x c, sehingga: Sc = -D (15) Jika sekarang kita menyatakan ⁄ dalam ᵮ, menggunakan persamaan 15, maka kita memperoleh: S = -= × ᵮ (16) Terdapat satu kasus ketika kita sudah mengetahui kecepatan hanyut dan gaya efektif yang bekerja pada partikel: ion dalam larutan mempunyai kecepatan hanyut s = µE jika ion itu mengalami gaya еɀE, dan ɀFE per mol, dari medan listrik dengan kuat medan E (210)(211)(212).…”
Section: Hantaranunclassified